Development of Kinetics Model for Torrefaction of Logging Residue and Palm Oil Waste - Nur Hazirah Huda, Mohd Harun (2016)
Torrefaction is a mild thermal (200-300°C) pretreatment in an inert atmosphere used to upgrade the fuel properties of biomass. During torrefaction process, biomass is thermally decomposed at a lower rate which leads to an anhydrous weight loss (AWL) of biomass. Considering the properties of torrefied biomass usually depending on the AWL, hence a model to estimate the AWL is then become necessary in order to produce the desired properties of torrefied biomass in the torrefaction process. Therefore the objective of this work is to examine two step reaction in series model that can be used to predict the AWL for two different types of biomass. Two types of biomasses used are sawdust from logging residue and empty fruit bunch (EFB) which is a type of palm oil wastes. In this work, a two step reaction in series model developed by Di Blasi and Lanzetta is examined to model the AWL of logging residue and palm oil waste. In this proposed model, kinetics of all reactions is assumed to follow an Arrhenius law with two parameters namely activation energy and kinetic rate constant. These parameters are adjusted in order to fit the predicted AWL to the experimental AWL using nonlinear optimization ‘lsqcurvefit’ routine in Matlab. Here the sets of experimental data of AWL for sawdust and EFB are based on the different temperature at 240, 270 and 300°C at 10°C/min of heating rate which are obtained from thermogravimetric analysis (TGA). The results show the kinetic parameters estimated using two step reaction in series model give a good agreement in terms of the coefficient determination (R2) for both palm oil and logging residue and thus can be employed to optimize the torrefaction process in the pilot and industrial scales.